Insight into single-fiber push-out test of tungsten fiber-reinforced tungsten. Issue 2 (1st February 2019) - Schönen, Stephan; Jasper, Bruno; Coenen, Jan Willem; Du, Juan; Höschen, Till; Riesch, Johann; Natour, Ghaleb; Neu, Rudolf; Linsmeier, Christian
ABSTRACT: To overcome the intrinsic brittleness of tungsten (W), a tungsten fiber-reinforced tungsten-composite material (Wf /W) is a possible solution. The introduction of energy dissipation mechanisms like fiber bridging or fiber pull-out by means of an engineered interface between fiber and matrix mitigate the brittleness of tungsten and lead to a pseudo-ductile material behaviour. The push-out test of single-fiber samples is an experimental method to investigate the properties of the interface between fiber and matrix of composite materials. It is widely used for the investigation of ceramic composites. This method was also used to investigate the debonding and frictional properties of the Er2 O3 interface region between fiber and matrix of Wf /W single-fiber samples made by CVDand HIP-processes. In this article finite element calculations are used to get a better understanding of the processes acting in the interface during a push-out test of Wf /W. A detailed overview of the debonding progress and of the corresponding stress states of the interface during the different stages of the test is presented. In addition the sensitivity of the push-out behaviour regarding the different interface properties and the plastic flow curve of the tungsten fiber are investigated. Graphical Abstract: